1997
DOI: 10.1172/jci119161
|View full text |Cite
|
Sign up to set email alerts
|

Acute bacterial pneumonia in rats increases alveolar epithelial fluid clearance by a tumor necrosis factor-alpha-dependent mechanism.

Abstract: To study the rate and regulation of alveolar fluid clearance in acute pneumonia, we created a model of Pseudomonas aeruginosa pneumonia in rats. To measure alveolar liquid and protein clearance, we instilled into the airspaces a 5% bovine albumin solution with 1.5 Ci of 125 I-human albumin, 24 h after intratracheal instillation of bacteria. The concentration of unlabeled and labeled protein in the distal airspaces over 1 h was used as an index of net alveolar fluid clearance. Since there was histologic evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
118
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(131 citation statements)
references
References 58 publications
12
118
1
Order By: Relevance
“…fluid clearance, was preserved in a bacteria-induced model of acute lung injury [21] in which decreases in both VEGF mRNA and VEGF protein were shown [5]. The number of alveolar type II epithelial cells was increased, in keeping with previous studies in ARDS demonstrating similar increases in numbers, as well as elevation of epithelial growth factors [1,22,23].…”
Section: Vascular Endothelial Growth Factor and Ards Y Abadie Et Alsupporting
confidence: 86%
“…fluid clearance, was preserved in a bacteria-induced model of acute lung injury [21] in which decreases in both VEGF mRNA and VEGF protein were shown [5]. The number of alveolar type II epithelial cells was increased, in keeping with previous studies in ARDS demonstrating similar increases in numbers, as well as elevation of epithelial growth factors [1,22,23].…”
Section: Vascular Endothelial Growth Factor and Ards Y Abadie Et Alsupporting
confidence: 86%
“…Notably, in the present study, the biphasic modulation of α-ENaC expression, with an increase at 8 h followed by a decrease thereafter, may explain the contradictory reports concerning ENaC expression following endotoxin or bacteria infection in the lung. Instillation of endotoxin into rat lungs and acute bacterial pneumonia in rats has been found to upregulate sodium transport and increase alveolar epithelial fluid clearance (21,22). However, in late pneumonia or severe ALI with pulmonary edema, a significant decrease in α-ENaC expression has been identified, which is associated with a reduced ability for lung fluid clearance (22).…”
Section: Discussionmentioning
confidence: 99%
“…2, 9, and 10) are not presently known. However, Rezaiguia et al (52) demonstrated that acute pneumonia with PA in rats increases fluid clearance from the lung, a process that is associated with acute lung injury. Additional studies should determine whether CFTR has a role in the coordination of fluid dynamics and host-pathogen interactions during PA pneumonia.…”
Section: Discussionmentioning
confidence: 99%